Makna Qasidah Muhammadiyah pada Bait ke 1-10 Karya Imam Bushiri (Analisis Semiotika Riffatere) - Rahman, Ahmad Fahri; Kholil, Mohammad Farhan (Universitas Syiah Kuala, 2025)
This study aims to analyze the meaning of the Qasidah Muhammadiyah by Imam AlBusyiri through Michael Riffaterres semiotic approach. A qualitative descriptive method with heuristic and hermeneutic reading techniques was employed to identify the matrix, model, and variant meanings within the poem. The findings reveal that this poem contains complex literal and symbolic meanings portraying Prophet Muhammad as a figure of glory, virtue, and spiritual enlightenment for humanity. Utilizing Riffaterres theory, the study successfully unveils hidden layers of meaning and symbolic structures underpinning the religious and aesthetic values of the poem. The implications of this research enrich religious literary studies and offer a methodological alternative for analyzing Islamic literary works.